The uppermost Middle and Upper Albian succession at the Col de Palluel, Hautes-Alpes, France: An integrated study (ammonites, inoceramid bivalves, planktonic foraminifera, nannofossils, geochemistry, stable oxygen and carbon isotopes, cyclostratigraphy) - Gale, A; Bown, P; Caron, M; Crampton, J; Crowhurst, S; Kennedy, W; Petrizzo, MR; Wray, D (2011)
An integrated study of the ammonites, inoceramid bivalves, planktonic foraminifera, calcareous nannofossils, geochemistry, stable carbon isotopes, and cyclostratigraphy is provided for the upper Middle to upper Upper Albian sucession exposed in the Col de Palluel section east of Rosans in Hautes-Alpes, France. The Albian-Cenomanian boundary interval described by Gale et al. at Mont Risou is re-examined, a total thickness of 370 m of the Marnes Bleues Formation. Zonal schemes based on ammonites, inoceramid bivalves, planktonic foraminifera, and calcareous nannofossils are integrated with the stable carbon isotope curve and key lithostratigraphic markers to provide a sequence of more than 70 events in the uppermost Middle Albian to basal Cenomanian interval. Time series analysis of the Al2O3 content of the 500 m Albian sequence present in the Col de Palluel and Risou sections reveals the presence of the 20 kyr precession, 40 kyr tilt, 100 kyr short eccentricity, and 406 kyr long eccentricity cycles. Correlation using planktonic foraminiferan and nannofossil data provide a link between the Col de Palluel and Risou sections and the Italian sequence at Gubbio, and in the Piobbico core. This provides a basis for the extension of the orbital time scale of Grippo et al. to the sequence. It reveals a major break in the Col de Palluel succession at the top of the distinctive marker bed known as the Petite Vérole that may represent as much as 2 Ma. It also provides a basis for the estimation of the length of the Albian Stage at 4.12Ma, 0.8 Ma for the early Albian, 2.84 Ma for the Middle Albian, and 3.68 Ma for the late Albian substages. © 2010 Elsevier Ltd.